An Exploration of Family and Juvenile Justice Systems to Reduce Youth HIV/STI Risk. (13th September 2014) - Elkington, Katherine S.; Belmonte, Kimberly; Latack, Jessica A.; Mellins, Claude Ann; Wasserman, Gail A.; Donenberg, Geri R.; Hirsch, Jennifer S.
Abstract : Using in‐depth interviews with 20 probation youth (60% female; 35% White; 30% Hispanic; mean age: 15 years, range = 13–17), their caregivers (100% female; mean age: 44 years, range = 34–71), and 12 female probation officers (100% White; mean age: 46 years, range = 34–57), we explored how family and probation systems exacerbate or mitigate sexual risk. We conducted thematic analyses of interviews, comparing narratives of families of sexually risky ( n = 9) versus nonsexually risky ( n = 11) youth. Family functioning differed by youth sexual risk behavior around quality of relationships, communication, and limit setting and monitoring. The involvement of families of sexually risky youth in probation positively influenced family functioning. Data suggest that these families are amenable to intervention and may benefit from family‐based HIV/STI interventions delivered in tandem with probation.